Access denied a study on the utilization of the online media by public secondary publications in the National Capital Region - Cabalza, Dexter V. (2014)
"This study explained the inability of public secondary school publications in Metro Manila to utilize online media specifically the website and the social media. Survey results showed that the campus publication staff had the knowledge to utilize online media based on their age, journalism and information technology trainings and online activity. While the school paper advisers and editors-in-chief also shared a positive perception in integrating online media with their campus publications, they did not efficiently utilize the feature of online media. The researcher found only onw website and seven social media accounts of the publications from five schools. Analysis showed that majority of these showed little or no activity. Interviews revealed that school paper advisers lacked the training both in journalism and in information and communication technology. Trainings for online journalism were also not prioritized compared to other categories in the schools press conference. In addition, schools were found out to be lacking working computers and internet connection. The Department of Education has yet to institutionalize and develop online journalism and campus journalism in general."